Efficacy of different ovulation synchronization protocols on estrus induction response and conception rate in acyclic and cyclic crossbred cows - Dhami, Arjun J; Prajapati, Ashok R; Hadiya, Kamlesh K; Patel, Jagdish A; Prajapati, Jignesh P (Indian Journal of Dairy Science, 2019)
A study was carriedout under field conditions on 50 acyclic/anestrus and 50 cyclic/ repeat breeder HF crossbred cows to evaluate the efficacy of four standard estrus induction/ ovulation synchronization protocols, viz., Ovsynch (GPG), Ovsynch Plus (PMSG+GPG), Doublesynch (P-GPG) and Estradoublesynch (P-GPE) (10 cows in each protocol, and in untreated controls) in terms of estrus induction response and conception rates at induced estrus with fixed time AI (FTAI) and overall of 3 cycles. All the selected animals received pre-synchronization treatment, viz., Inj. Ivermectin and Tono-vita once i/m and multimineral bolus 1 daily for 7 days. Repeat breeding cows received additional single shot i/m injection of Enrofloxacin. All the anestrus and repeat breeder cows (100 %) under all four treatment protocols exhibited induced estrus within 48-72 hrs from PGF2Î± injection. The conception rates obtained in anestrus cows at induced estrus (FTAI) and overall of three cycles post-treatment were 20.0 and 60.0 % with Ovsynch; 20.0 and 50.0 % with Ovsynch Plus; 40.0 and 80.0 % with Doublesynch, and 30.0 and 60.0 % with Estradoublesynch protocol, respectively. The corresponding conception rates in repeat breeder cows were 30.0 and 70.0 % with Ovsynch; 30.0 and 50.0 % with Ovsynch Plus; 40.0 and 80.0 % with Doublesynch, and 20.0 and 60.0 % with Estradoublesynch protocol, respectively. All non-conceived repeat breeding cows under each protocol, except 1 in Ovsynch Plus protocol, continued cycling, while among 10 anestrus cows each treated with Ovsynch, Ovsynch Plus, Doublesynch and Estradoublesynch protocol, 2, 2, 0 and 1 cows again turned out to be anestrus by 60 days post-induction/FTAI, respectively. Among the untreated control anestrus and repeat breeder cows (10 each), 2 and 3 cows conceived over a period of 90 days follow up giving overall conception rates of only 20.0 and 30.0 %, respectively, as against the overall fertility rate of 62.50 and 65.00 % in treated anestrus and repeat breeder cows, respectively, over just mean 28-32 days of treatment, suggesting the economic utility of these protocols in handling the problem breeder cows under field conditions.